Frequency of the IVS-10nt546 mutation in 44 Turkish phenylketonuria patients - Özgüç, Meral; Özalp, İmran; Coşkun, Turgay; Yılmaz, Engin; Erdem, Hayat; Ayter, Şükrüye (The Turkish Journal of Pediatrics, 1993)
The newly identified point mutation in intron 10 of the phenylalanine hydroxylase gene activates a cryptic splice site and results in an in-frame insertion of nine nucleotides between exons 10 and 11 of the processed transcript. This mutation is observed in association with haplotype 6 of phenylketonuria chromosomes. Since in Turkey, haplotype 6 is observed in 40 percent of mutant phenylketonuria alleles, the aim of this study was to establish the incidence of this particular mutation. Forty-four classical phenylketonuria patients were studied and the frequency of the intron 10 splicing mutation was determined to be 31 percent.
Keywords: phenylketonuria; IVS-10nt546 mutation